Catalyst for the production of carboxylic acid esters, method for the production of carboxylic acid esters, and method for the production of a catalyst for the production of carboxylic acid esters

KR103018998B1Active Publication Date: 2026-09-11
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
KR1020237032422
Authority / Receiving Office
KR · KR
Patent Type
Patents
Filing Date
2021-03-26
Publication Date
2026-09-11
Estimated Expiration
2041-03-26

Smart Images

  • Figure 112023104748812-PCT00001
    Figure 112023104748812-PCT00001
Patent Text Reader

Abstract

A catalyst for producing a carboxylic acid ester comprising catalytic metal particles and a support supporting said catalytic metal particles, wherein the bulk density of said catalyst for producing the carboxylic acid ester is 0.50 g / cm³ or more and 1.50 g / cm³ or less, and when the particle diameter at which the cumulative frequency of the particle diameter distribution based on volume of said catalyst for producing the carboxylic acid ester is x% is denoted as Dx, D10 / D50≥0.2 and D90 / D50≤2.5, and when the half-width of said particle diameter distribution is denoted as W, W / D50≤1.5.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a catalyst for the production of a carboxylic acid ester, a method for the production of a carboxylic acid ester, and a method for the production of a catalyst for the production of a carboxylic acid ester. Background Technology

[0002] Nickel or nickel compounds are widely used as catalysts for chemical synthesis, such as oxidation, reduction, and hydrogenation reactions. Recently, catalytic oxygen oxidation reactions of alcohols have been realized through various modifications and improvements of nickel-based catalysts. However, in the chemical industry, it is known that nickel and nickel compounds are not limited to the oxidation of alcohols but are widely effective in various reactions, including oxidation, reduction, and hydrogenation, as well as in applications such as catalysts for automobile exhaust gas purification and photocatalysts.

[0003] For example, as a method for producing carboxylic acid esters, Patent Document 1 proposes using a composite particle support as a catalyst, comprising a composite particle composed of nickel in an oxidized state and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper) and a support that supports the composite particle, and having a support layer in which the composite particle is localized. It is stated that such a catalyst can maintain high reactivity over a long period of time.

[0004] Patent Document 2 describes spherical silica particles containing aluminum and magnesium, wherein the specific surface area, pore volume, pore distribution, bulk density, wear resistance, average particle diameter, aluminum content, and magnesium content are within a predetermined range. According to the document, it is stated that spherical silica-based particles can be provided that are capable of being used in a wide range of applications including catalyst carriers, have high mechanical strength, a large specific surface area, and good fluidity. Prior art literature

[0005] Japanese Patent Publication No. 4803767 Japanese Patent Publication No. 4420991 The problem to be solved

[0006] In the production of carboxylic acid esters using the catalysts described in Patent Documents 1 and 2, an improvement in catalytic activity is required, and thus a catalyst exhibiting a higher conversion rate is required. As a result of repeated experiments on the production of carboxylic acid esters, the inventors discovered that when carboxylic acid esters are produced over a long period using the catalysts described in Patent Documents 1 and 2, the conversion rate of the raw material tends to gradually decrease. Upon further investigation into the cause, it was found that the leakage of the catalyst from the reactor or the fluidity of the catalyst affects the conversion rate of the raw material. Furthermore, while the addition rate of the raw material or the selectivity of the carboxylic acid ester can be improved by increasing the amount of air blown in during the production of carboxylic acid esters, if the catalyst is prone to leaking out of the reactor, the effect of catalyst leakage becomes more pronounced as the amount of air blown increases, which can also hinder the improvement of reaction performance.

[0007] The present invention is made in consideration of the problems of the aforementioned prior art and aims to provide a catalyst for producing carboxylic acid esters that exhibits high activity while suppressing catalyst leakage. means of solving the problem

[0008] The inventors have bulk density and particle size distribution (D 10 / D 50 , D 90 / D 50 and W / D 50 The present invention was completed by discovering that the above problem can be solved by setting ) to a predetermined range.

[0009] That is, the present invention includes the following aspects.

[0010] [1]

[0011] A catalyst for producing a carboxylic acid ester comprising catalytic metal particles and a carrier supporting said catalytic metal particles,

[0012] The bulk density of the catalyst for producing the above-mentioned carboxylic acid ester is 0.50 g / cm³ or more and 1.50 g / cm³ or less, and

[0013] D is the particle diameter at which the cumulative frequency of the volume-based particle size distribution of the catalyst for the production of the above carboxylic acid ester is x%. x When doing D 10 / D 50 ≥0.2 and D 90 / D 50 ≤2.5 and,

[0014] When W is the full width at half maximum of the above particle size distribution, W / D 50 Catalyst for the production of carboxylic acid esters, with a value of ≤1.5.

[0015] [2]

[0016] A catalyst for producing a carboxylic acid ester as described in [1], wherein W is 100 μm or less.

[0017] [3]

[0018] A catalyst for producing carboxylic acid esters as described in [1] or [2], wherein the catalyst metal particles comprise at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, and gold, silver, and copper.

[0019] [4]

[0020] A catalyst for producing carboxylic acid esters as described in any one of [1] to [3], wherein the catalyst metal particles are composite particles comprising nickel and / or cobalt in an oxidized state and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper).

[0021] [5]

[0022] A catalyst for producing carboxylic acid esters as described in [4], wherein the composition ratio of nickel or cobalt and X in the above composite particles is 0.1 to 10 as the Ni / X atomic ratio or Co / X atomic ratio.

[0023] [6]

[0024] The above composite particles are a catalyst for producing carboxylic acid esters as described in [4] or [5], comprising nickel or cobalt in an oxidized state and gold.

[0025] [7]

[0026] A catalyst for producing a carboxylic acid ester as described in any one of [4] to [6], wherein the average particle diameter of the composite particles is 2 to 10 nm.

[0027] [8]

[0028] A carboxylic acid ester production catalyst described in any one of [4] to [7], wherein the supporting layer in which the above composite particles are localized exists from the surface of the carboxylic acid ester production catalyst to an area up to 40% of the substantial diameter of the carboxylic acid ester production catalyst.

[0029] [9]

[0030] A catalyst for producing a carboxylic acid ester according to any one of [4] to [8], wherein the above-mentioned equivalent diameter is 200 μm or less, and the supporting layer on which the above-mentioned composite particles are localized exists in an area from the surface of the catalyst for producing a carboxylic acid ester to 30% of the above-mentioned equivalent diameter of the catalyst for producing a carboxylic acid ester.

[0031]

[10]

[0032] A catalyst for producing a carboxylic acid ester as described in any one of [4] to [9], having an outer layer that substantially does not contain the composite particles on the outer side of a supporting layer in which the composite particles are localized, and the outer layer is formed with a thickness of 0.01 to 15 μm.

[0033]

[11]

[0034] A catalyst for producing a carboxylic acid ester as described in any one of [4] to

[10] , wherein the above composite particle has a nucleus composed of X, and the nucleus is coated with nickel or cobalt in an oxidized state.

[0035]

[12]

[0036] A catalyst for producing carboxylic acid esters as described in any one of [1] to

[11] , wherein the carrier comprises silica and alumina.

[0037]

[13]

[0038] The above D 50 A catalyst for producing a carboxylic acid ester described in any one of [1] to

[12] , having a thickness of 10 μm or more and 200 μm or less.

[0039]

[14]

[0040] A method for producing a carboxylic acid ester, comprising the process of reacting (a) an aldehyde with an alcohol or (b) one or more alcohols in the presence of oxygen and a catalyst for producing a carboxylic acid ester described in any one of [1] to

[13] .

[0041]

[15]

[0042] The above aldehyde is acrolein and / or metacrolein, a method for producing a carboxylic acid ester as described in

[14] .

[0043]

[16]

[0044] A method for preparing a carboxylic acid ester as described in

[14] or

[15] , wherein the aldehyde is acrolein and / or metacrolein and the alcohol is methanol. Effects of the invention

[0045] According to the present invention, a catalyst for producing carboxylic acid esters that exhibits high activity while suppressing the leakage of the catalyst can be provided. Specific details for implementing the invention

[0046] Hereinafter, embodiments of the present invention (hereinafter also referred to as "the present embodiments") will be described in detail. Furthermore, the present invention is not limited to the present embodiments described below and may be implemented with various modifications within the scope of its gist.

[0047] [Catalyst for the production of carboxylic acid esters]

[0048] The catalyst for producing a carboxylic acid ester according to the present embodiment is a catalyst for producing a carboxylic acid ester comprising catalyst metal particles and a support supporting said catalyst metal particles, wherein the bulk density of said catalyst for producing a carboxylic acid ester is 0.5 g / cm³ or more and 1.5 g / cm³ or less, the full width at half maximum of the particle size distribution based on volume of said catalyst for producing a carboxylic acid ester is 100 μm or less, and the particle diameter at which the cumulative frequency of the particle size distribution based on volume of said catalyst for producing a carboxylic acid ester becomes x% is D x When doing D 10 / D 50 ≥0.2 and D 90 / D 50 When ≤2.5 and W is the full width at half maximum of the volume-based particle size distribution, W / D 50 ≤1.5. Because it is configured in this way, the catalyst for producing carboxylic acid esters according to the present embodiment exhibits high activity while suppressing the outflow of the catalyst.

[0049] In the present embodiment, the bulk density of the catalyst for producing carboxylic acid esters is 0.50 g / cm³ or higher and 1.50 g / cm³ or lower. Although the above bulk density is thought to have little relation to the problem of reduced catalyst activity, it is believed that by adjusting the above bulk density to the above range, the catalyst becomes easier to diffuse within the reactor, thereby increasing the conversion rate of the raw material. That is, if the bulk density is lower than the above lower limit, the catalyst flows out of the reactor during long-term operation, and the amount of catalyst decreases, resulting in lower activity; and if the bulk density is higher than the above upper limit, the catalyst's circulation is low, which impairs the opportunity for contact with the raw material, resulting in lower activity. From this perspective, it is preferable that the bulk density of the catalyst for producing carboxylic acid esters be 0.70 g / cm³ or higher and 1.30 g / cm³ or lower, and more preferably 0.90 g / cm³ or higher and 1.20 g / cm³ or lower.

[0050] The above volume density can be measured by the method described in the examples below.

[0051] The above volume density can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described later.

[0052] D is the particle diameter at which the cumulative frequency of the volume-based particle size distribution of catalysts for the production of carboxylic acid esters becomes x%. x When doing D 10 / D 50 is 0.2 or greater. D 10 / D 50 As a catalyst for the production of carboxylic acid esters, it is an indicator representing the extent to which particles with small diameters exist relative to the average particle diameter, and the closer this value is to 1.0, the sharper the distribution on the small particle side has become. In this embodiment, D 10 / D 50 Since this is 0.2 or higher, the fluidity of the catalyst for the production of carboxylic acid esters increases, and high activity is expressed. In the same regard, D 10 / D50 It is desirable that the value be 0.3 to 0.8.

[0053] D 10 / D 50 It can be measured by laser diffraction and scattering methods, and more specifically, by the method described in the examples below.

[0054] D 10 / D 50 It can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described below.

[0055] In this embodiment, D 90 / D 50 is 2.5 or higher. It is an indicator representing the extent to which large-diameter particles exist relative to the average particle diameter as a catalyst for the production of carboxylic acid esters, and the closer this value is to 1.0, the sharper the distribution on the opposite side has become. In this embodiment, D 90 / D 50 Since this is 2.5 or higher, the fluidity of the catalyst for the production of carboxylic acid esters increases, and high activity is exhibited. In the same regard, D 90 / D 50 It is desirable that the value be 1.4 to 2.3.

[0056] D 90 / D 50 It can be measured by laser diffraction and scattering methods, and more specifically, by the method described in the examples below.

[0057] D 90 / D 50 It can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described below.

[0058] When W is the full width at half maximum of the volume-based particle size distribution of a catalyst for the production of carboxylic acid esters, W / D 50 is 1.5 or less. W / D 50is an indicator showing how much the peak full width at half maximum in the above particle size distribution is widened relative to the average particle diameter, and the smaller this value, the sharper the distribution. In this embodiment, W / D 50 Since α is 1.5 or less, the fluidity of the catalyst for the production of carboxylic acid esters is increased while suppressing catalyst leakage, and high activity is exhibited while suppressing catalyst leakage. In addition, when there are multiple peaks in the above particle size distribution, W corresponding to the highest peak is considered to satisfy the above relationship. In the same regard, W / D 50 It is desirable that the value be 0.6 to 1.3.

[0059] W / D 50 It can be measured by laser diffraction and scattering methods, and more specifically, by the method described in the examples below.

[0060] W / D 50 It can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described below.

[0061] In the present embodiment, it is preferable that the above W be 100 μm or less. By setting the value of W to 100 μm or less, the outflow of the catalyst tends to be further suppressed. Although it is thought that the above half-width, as well as the above bulk density, have little relation to the problem of the decrease in catalyst activity, by adjusting the above half-width to the above range, the outflow of the catalyst from the reactor is prevented, and furthermore, the conversion rate of the raw material tends to increase along with this. In addition, it is a novel finding that the outflow of the catalyst from the reactor to the extent that it affects the conversion rate of the raw material is due to the particle size distribution of the catalyst.

[0062] From the same perspective, it is more preferable that W be 5 μm or more and 95 μm or less, and even more preferable that W be 10 μm or more and 90 μm or less.

[0063] W can be measured by laser diffraction and scattering methods, and more specifically, by the method described in the examples below.

[0064] W can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described below.

[0065] D in this embodiment 50 It is preferable that the size is 10 µm or more and 200 µm or less, more preferable that it is 20 µm or more and 150 µm or less, even more preferable that it is 40 µm or more and 100 µm or less, and even more preferable that it is 40 µm or more and 80 µm or less. D 50 By setting the above range, there is a tendency to obtain a catalyst for producing carboxylic acid esters that exhibits higher activity while further suppressing the efflux of the catalyst.

[0066] D 50 It can be measured by laser diffraction and scattering methods, and more specifically, by the method described in the examples below.

[0067] D 50 It can be adjusted to the above-described range by, for example, adopting the preferred manufacturing conditions described below.

[0068] In the present embodiment, it is preferable that the particle size distribution of the catalyst be a single peak. If the particle size distribution is a single peak, it means that in the particle size distribution based on volume, there are no peaks other than 1 / 5 of the highest peak.

[0069] In the present embodiment, the catalyst metal particles are not particularly limited as long as they have the function of catalyzing a reaction for producing a carboxylic acid ester, but from the perspective of catalytic performance, it is preferable to include at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, gold, silver, and copper. Furthermore, from the perspective of further catalytic performance, it is more preferable that the catalyst metal particles be composite particles comprising nickel and / or cobalt in an oxidized state and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper), and it is even more preferable that the composite particles include nickel or cobalt in an oxidized state and gold.

[0070] In the present embodiment, the catalyst for producing carboxylic acid esters preferably has a support layer in which composite particles are localized. The term "support layer in which composite particles are localized" refers to a region within the carrier where composite particles are concentratedly supported. In the catalyst for producing carboxylic acid esters according to the present embodiment, it is preferable that the composite particles are not randomly supported within the carrier but are selectively supported in a specific region, and this region is referred to as the "support layer in which composite particles are localized." In the catalyst for producing carboxylic acid esters, if composite particles are concentrated in a specific region compared to other parts, that region is the "support layer in which composite particles are localized." Therefore, which region constitutes the "support layer in which composite particles are localized" can be identified by the X-ray microprobe analysis method described later or by the secondary electron reflection image of a high-resolution scanning electron microscope. It is preferable that the support layer localized with composite particles exists in a region extending from the surface of the catalyst for producing carboxylic acid esters to 40% of the substantial diameter of the catalyst for producing carboxylic acid esters. When the support layer localized with composite particles exists in the above region, the influence of the diffusion rate of the reaction material within the support is reduced, and the reaction activity tends to be improved.

[0071] The catalyst for producing carboxylic acid esters according to the present embodiment may have various sizes and shapes with a substantial thickness or particle diameter on the order of μm to cm. Specific examples of the shape of the catalyst for producing carboxylic acid esters include, but are not limited to, spherical, elliptical, cylindrical, tablet-shaped, hollow cylindrical, plate-shaped, rod-shaped, sheet-shaped, honeycomb-shaped, etc. These shapes can be appropriately changed according to the reaction type, and, but are not limited to, for example, in a stationary phase reaction, a hollow cylindrical or honeycomb-shaped shape with low pressure loss is selected, and in liquid phase slurry-suspension conditions, a spherical shape is generally selected.

[0072] The term "equivalent diameter" as used herein refers to the diameter of a spherical particle, or, in the case of irregularly shaped particles, the diameter of a sphere of equal volume to the particle or a sphere having the same surface area as the particle. The method for measuring the equivalent diameter is to use a laser diffraction and scattering particle size distribution measuring device D 50 Measure it and make it the equivalent diameter.

[0073] The thickness of the support layer localized with composite particles is selected within an optimal range depending on the thickness of the support, particle diameter, type of reaction, and reaction format. Additionally, since the "equivalent diameter of the catalyst for producing carboxylic acid esters" is typically equal to the "equivalent diameter of the support," the "equivalent diameter of the catalyst for producing carboxylic acid esters" can be determined by the equivalent diameter of the support.

[0074] Meanwhile, when the equivalent diameter of the catalyst for producing carboxylic acid esters is 200 μm or less, it is preferable to support the composite particles in the region from the surface of the catalyst for producing carboxylic acid esters to 30% of the equivalent diameter of the catalyst for producing carboxylic acid esters. In particular, when used in a liquid-phase reaction, the reaction rate and the diffusion rate of the reactant within the pores of the support are affected; therefore, conventionally, the design has been made to reduce the particle diameter of the support to match the reaction. In this embodiment, by making the support layer in which the composite particles are localized thin, a catalyst for producing carboxylic acid esters with high activity can be obtained without reducing the particle diameter of the support. In this case, there is also the advantage that the separation of the catalyst by sedimentation becomes easy, allowing separation to be performed using a small-capacity separator. On the other hand, if the volume of the portion of the catalyst for producing carboxylic acid esters where the composite particles are not supported becomes excessively large, the volume unnecessary for the reaction per reactor increases, which may result in waste. Therefore, it is desirable to set the diameter of the carrier particles according to the type of reaction, and to set the thickness of the supporting layer where the required composite particles are localized and the thickness of the layer where the composite particles are not supported.

[0075] A catalyst for the production of carboxylic acid esters may have an outer layer that substantially does not contain composite particles on the outer side of a supporting layer in which composite particles are localized. It is preferable that the outer layer be formed with a thickness of 0.01 to 15 μm from the outer surface of the support. By having an outer layer within this range, the catalyst can be used as a catalyst that is resistant to catalyst poisoning and suppresses the detachment of composite particles due to wear in reactions using reactors where friction of catalyst particles is a concern, such as fluidized beds, bubble towers, and stirred reactors, or in reactions where poisoning substances accumulate. In addition, since the outer layer can be controlled to be very thin, a significant decrease in activity can be suppressed.

[0076] The thickness of the outer layer that does not substantially contain composite particles is selected within an optimal range depending on reaction characteristics, carrier properties, and the amount of composite particles loaded, and is preferably 0.01 to 15 μm, more preferably 0.1 to 10 μm, and even more preferably 0.2 to 5 μm. If the thickness of the outer layer (layer not loaded with composite particles) exceeds 15 μm, the effect of improving the lifespan of the catalyst does not change when the composite particles are used as a catalyst, but it may result in a decrease in catalyst activity. If the thickness of the outer layer is less than 0.01 μm, there is a tendency for the composite particles to detach easily due to wear.

[0077] In this embodiment, the term “substantially not containing composite particles” means that in the X-ray microprobe analysis method described later or the secondary electron reflection image of a high-resolution scanning electron microscope, there is substantially no peak showing the distribution of nickel and / or cobalt in an oxidation state with a relative intensity of 10% or more and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper).

[0078] The nickel in an oxidized state that can constitute the composite particles in the present embodiment is preferably a nickel oxide formed by combining nickel with oxygen (e.g., Ni2O, NiO, NiO2, Ni3O4, Ni2O3), or a nickel oxide compound or solid solution formed by combining nickel with X and / or one or more other metal elements with oxygen, or a complex oxide containing nickel such as a mixture thereof.

[0079] In addition, the oxidized cobalt that can constitute the composite particle in the present embodiment is preferably a composite oxide containing cobalt, such as a cobalt oxide (e.g., CoO, Co2O3, Co3O4) formed by combining cobalt with oxygen, or a cobalt oxide compound or solid solution formed by combining cobalt with X and / or one or more other metal elements, or a mixture thereof.

[0080] The term "nickel oxide" as used herein refers to a compound containing nickel and oxygen. Nickel oxide includes the above-mentioned Ni2O, NiO, NiO2, Ni3O4, Ni2O3 or their hydrates, nickel hydroperoxide containing an OOH group, nickel peroxide containing an O2 group, or mixtures thereof.

[0081] In addition, the term “complex oxide” as used herein refers to an oxide containing two or more metals. “Complex oxide” is an oxide in which two or more metal oxides form a compound, and includes complex oxides in which oxo-oxide ions are not present as structural units (e.g., nickel perovskite-type oxide or spinel-type oxide), but it is a broader concept than complex oxide and includes all oxides in which two or more metals are complex. Oxides in which two or more metal oxides form a solid solution are also in the category of complex oxides.

[0082] In the catalyst for producing carboxylic acid esters according to the present embodiment, when nickel oxide and / or cobalt oxide are combined with X as described above, the inherent catalytic activity of the nickel oxide and / or cobalt oxide, which possess oxidative esterification activity, is derived, and there is a tendency for significantly high catalytic performance to appear that could not be realized with catalysts containing each single component. This is a unique effect manifested by combining nickel oxide and / or cobalt oxide with X, and it is believed that a new catalytic action entirely different from that of each single component arises due to dual functional effects between the two metal components or the generation of new active species. Furthermore, when nickel in an oxidized state and / or cobalt in an oxidized state and X are supported on a carrier in a highly dispersed state, there is a tendency to realize groundbreaking catalytic performance that cannot be obtained with conventional catalysts.

[0083] For example, if gold is selected as X and nickel oxide and gold are highly dispersed and supported on a support, significant and high catalytic performance tends to appear. Compared to catalysts in which nickel oxide or gold is supported as a single unit on a support, such catalysts for the production of carboxylic acid esters exhibit high selectivity for carboxylic acid esters and show a tendency for significantly improved activity at a specific Ni / Au composition ratio. Regarding catalytic activity per metal atom, they show higher activity compared to particle supports containing each single component, and the manifestation of catalytic function through their complexation strongly depends on the nickel and gold support composition. This is presumed to be because there exists an optimal ratio for the formation of the nickel oxidation state that is optimal for the reaction. As such, by dispersing and supporting the two components of nickel oxide and gold on a support, excellent complex effects that cannot be expected with only simple addition of each single component tend to be manifested.

[0084] As described above, the catalyst for producing carboxylic acid esters, in which gold is selected as X, has nickel and gold in an oxidized state highly dispersed and supported on a support, and both components tend to be complexed into nano-sized components. When such a catalyst for producing carboxylic acid esters is observed using a transmission electron microscope / scanning transmission electron microscope (TEM / STEM), a structure is observed in which typically nearly spherical nanoparticles of 2 to 3 nm are uniformly dispersed and supported on a support.

[0085] In addition, when subjected to elemental analysis of nanoparticles by energy dispersive X-ray spectroscopy (EDS), nickel and gold typically coexist in any particle, and it is observed that nickel is coated on the surface of gold nanoparticles, and in addition to nanoparticles containing nickel and gold, it is also observed that nickel components are supported as a monolith on a carrier.

[0086] In addition, the state of existence of the metal can be confirmed by applying X-ray photoelectron spectroscopy (XPS) and powder X-ray diffraction (powder XRD), and typically, gold is observed to exist as a crystalline metal, while nickel is observed to exist as an amorphous oxide with a divalent valence.

[0087] Furthermore, when subjected to ultraviolet-visible spectroscopy (UV-Vis), which can observe changes in the excited state of electrons, it is observed that the surface plasmon absorption peak (approx. 530 nm) originating from gold nanoparticles, which is typically observed in gold nanoparticles of a single metal species, disappears due to the complexation of nickel oxide and gold. This phenomenon of the disappearance of the surface plasmon absorption peak was not observed in catalysts containing a combination of gold and other metal oxide species other than nickel oxide (e.g., metal oxides such as chromium oxide, manganese oxide, iron oxide, cobalt oxide, copper oxide, and zinc oxide), which showed no effect in the reaction. This disappearance of the surface plasmon absorption peak is thought to be the result of hybridization of electronic states through the contact interface between the oxidized nickel and gold, that is, due to the hybridization of two types of metal chemical species.

[0088] In addition, the conversion to high-oxidation nickel oxide can be confirmed by the color change of the catalyst and ultraviolet-visible spectroscopy (UV-Vis). Upon the addition of gold to nickel oxide, the nickel oxide changes color from grayish-green to dark brown, and the UV spectrum shows absorption across almost the entire visible light region. The shape of the UV spectrum and the color of the catalyst are similar to those of high-oxidation nickel peroxide (NiO2) measured as a reference sample. Thus, it is inferred that nickel oxide is being converted into high-oxidation nickel oxide by the addition of gold.

[0089] From the above results, regarding the structure of the composite particle when gold is selected as X, it is thought that the structure is such that the gold particle is the nucleus and its surface is coated with nickel oxide in a high oxidation state, and that no gold atoms exist on the surface of the composite particle.

[0090] It is preferable that the composite particles be supported on a carrier in a highly dispersed state. It is more preferable that the composite particles be dispersed and supported in the form of fine particles or thin films, and the average particle diameter is preferably 2 to 10 nm, more preferably 2 to 8 nm, and even more preferably 2 to 6 nm.

[0091] If the average particle diameter of the composite particles is within the above range, a specific active species structure containing nickel and / or cobalt and X is formed, and the reaction activity tends to be enhanced. Here, the average particle diameter of the composite particles in this embodiment refers to the number-average particle diameter measured by a transmission electron microscope (TEM). Specifically, in an image observed by a transmission electron microscope, the black contrast area is the composite particle, and the number-average can be calculated by measuring the diameter of each particle.

[0092] The composition of nickel or cobalt and X in the composite particles is preferably in the range of 0.1 to 10 as the Ni / X atomic ratio or Co / X atomic ratio, more preferably in the range of 0.2 to 8.0, and even more preferably in the range of 0.3 to 6.0. When the Ni / X atomic ratio or Co / X atomic ratio is within the above range, it forms an oxidation state of nickel and / or cobalt that is optimal for the structure and reaction of specific active species containing nickel and / or cobalt and X, and as a result, the activity and selectivity tend to be higher than when it is outside the above range.

[0093] Regarding the shape of the composite particle, it is not particularly limited as long as both components of nickel and / or cobalt and X are included; however, it is preferable that both components coexist within the particle and form a shape having a phase structure, such as a solid solution structure where chemical species randomly occupy crystal sites, a core-shell structure where each chemical species is separated into concentric spheres, an anisotropic phase separation structure where phases are separated anisotropically, or a heterobondophilic structure where both chemical species exist adjacently on the particle surface. More preferably, it is desirable to have a nucleus containing X, and the surface of the nucleus is coated with nickel and / or cobalt in an oxidized state. Regarding the shape of the composite particle, it is not particularly limited as long as both components are included, and any shape such as spherical or hemispherical is acceptable.

[0094] As an interpretation method for observing the morphology of composite particles, transmission electron microscopes / scanning transmission electron microscopes (TEM / STEM), for example as described above, are effective. By irradiating the nanoparticles observed by TEM / STEM with electron beams, it becomes possible to analyze the elements within the particles or output an image display of the elemental distribution. It was confirmed that the composite particles in this embodiment, as shown in the examples described later, contain nickel and / or cobalt and X within each particle, and have a form in which the surface of X is coated with nickel and / or cobalt. When having this form, the atomic ratio of nickel and / or cobalt to X varies depending on the location of the composition analysis point within the particle, and more nickel and / or cobalt is detected at the edges of the particles than at the center. Therefore, even for individual particles, the atomic ratio of nickel or cobalt to X varies depending on the location of the analysis point, and the range falls within the range of the Ni / X atomic ratio or Co / X atomic ratio described above.

[0095] When gold, silver, and copper are selected as X, ultraviolet-visible spectroscopy (UV-Vis) is a powerful means for determining the structure. In a monolithic nanoparticle of gold, silver, and copper, the photoelectric field in the visible to near-infrared region couples with the surface free electrons of the metal, exhibiting surface plasmon absorption. For example, when visible light is irradiated onto a catalyst supported with gold particles, an absorption spectrum based on plasmon resonance originating from the gold particles is observed at a wavelength of approximately 530 nm. However, in the catalyst for manufacturing carboxylic acid esters supported with nickel oxide and gold of the present embodiment, the surface plasmon absorption is lost, so it can be assumed that gold does not exist on the surface of the composite particle in the present embodiment.

[0096] As for the solid form of nickel, it is not particularly limited as long as it can obtain a certain activity, but preferably it is an amorphous phase in which no diffraction peaks are observed in X-ray diffraction. By taking this form, it is presumed that when used as a catalyst for an oxidation reaction, the interaction with oxygen is increased, and furthermore, since the interface between nickel in the oxidized state and X increases, there is a tendency to obtain superior activity.

[0097] In the present embodiment, X is at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper. More preferably, it is selected from nickel, palladium, ruthenium, gold, and silver.

[0098] The chemical state of X may be any of a metal, an oxide, a hydroxide, a complex compound containing X and nickel, cobalt, or one or more other metal elements, or a mixture thereof, but the preferred chemical state is a metal or an oxide, more preferably a metal. In addition, the solid form of X is not particularly limited as long as it can obtain a desired activity, and may be in a crystalline or amorphous form.

[0099] The term “other metallic element” as used herein refers to a third component element or metallic component, such as an alkali metal, alkaline earth metal, and rare earth metal, contained in the catalyst for the production of carboxylic acid esters, in addition to the constituent elements of the carrier described below, nickel and / or cobalt in an oxidized state, and X.

[0100] The catalyst for producing carboxylic acid esters according to the present embodiment exhibits excellent effects by supporting nickel and / or cobalt in an oxidized state and X on a carrier as described above, thereby forming a composite particle composed of nickel and / or cobalt in an oxidized state and X. Furthermore, the term "composite particle" as used in the present embodiment refers to a particle containing another binary metal species within a single particle. Other binary metal species include binary metal particles in which both nickel and / or cobalt and X are metal components, metal particles forming an alloy or intermetallic compound of nickel and / or cobalt and X, etc. However, when these are used as catalysts for chemical synthesis, they tend to have lower selectivity for the target product and catalytic activity compared to the catalyst for producing carboxylic acid esters according to the present embodiment.

[0101] In the catalyst for producing carboxylic acid esters according to the present embodiment, it is preferable to contain nickel and / or cobalt in an oxidized state alone on a support, separate from the composite particles composed of nickel and / or cobalt in an oxidized state and X. By having nickel and / or cobalt in an oxidized state that is not complexed with X, the structural stability of the catalyst for producing carboxylic acid esters is further enhanced, and the increase in pore diameter due to long-term reaction and the accompanying particle growth of the composite particles are suppressed. This effect becomes significant when an aluminum-containing silica-based composition comprising silica and alumina is used as a support, as described below.

[0102] Below, we will explain the effect of increasing the structural stability of a catalyst for the production of carboxylic acid esters and suppressing the increase in pore diameter and the accompanying particle growth of composite particles caused by long-term reactions by having nickel and / or cobalt in an oxidized state present alone on a support.

[0103] As described below, in the synthesis reaction of carboxylic acid esters, by adding a compound of an alkali metal or an alkaline earth metal to the reaction system and maintaining the pH of the reaction system at 6 to 9, more preferably at neutral conditions (e.g., pH 6.5 to 7.5), that is, at around pH 7, it is possible to suppress by-products such as acetals caused by acidic substances, such as methacrylic acid or acrylic acid, which are by-products inherent to the reaction for producing carboxylic acid esters.

[0104] According to the inventors' review, when a gold particle support, comprising single-component gold particles supported on a carrier containing an aluminum-containing silica-based composition including silica and alumina, is subjected to a long-term reaction operation, structural changes in the gold particle support tend to occur, albeit gradually. This phenomenon is believed to be caused by the repeated localized exposure of the support particles to acids and bases during the reaction operation, which leads to the dissolution and precipitation of some of the Al within the carrier, resulting in a rearrangement of the silica-alumina cross-linking structure and consequently an expansion of the pore diameter of the support particles. Furthermore, accompanied by the expansion of the pore diameter, sintering of the gold particles occurs, and the resulting decrease in surface area tends to lead to a decline in catalytic activity.

[0105] Meanwhile, by presenting composite particles and nickel and / or cobalt in an oxidized state alone on a carrier, the structural stability of the supported particles resulting from the reaction operation is enhanced, and there is a tendency for the expansion of pore diameter and the growth of the composite particles to be suppressed. Regarding the reason for this, as described above, it is believed that the factor is that nickel and / or cobalt in an oxidized state reacts with the constituent elements of the carrier to generate complex oxides containing nickel and / or cobalt, such as nickel and / or cobalt oxide compounds or solid solutions. It is believed that as such nickel compounds acted to stabilize the silica-alumina cross-linking structure, the structural changes of the supported particles were significantly improved. The inventors presume that the manifestation of such structural stabilization effects of the carrier is attributed to the nickel and / or cobalt in an oxidized state present on the carrier. Therefore, when nickel and / or cobalt in an oxidized state included in the composite particles are in contact with the carrier, this effect is naturally obtained, and it is thought that an even greater stabilization effect can be obtained when nickel and / or cobalt in an oxidized state exist alone on the carrier.

[0106] As a carrier for the catalyst for producing carboxylic acid esters of the present embodiment, it is not particularly limited as long as it can support nickel and / or cobalt in an oxidized state and X, and a catalyst carrier used for conventional chemical synthesis may be used.

[0107] Examples of carriers include various carriers such as activated carbon, silica, alumina, silica-alumina, titania, silica-titania, zirconia, magnesia, silica-magnesia, silica-alumina-magnesia, calcium carbonate, zinc oxide, zeolite, and crystalline metallosilicate. Preferably, the carriers are activated carbon, silica, alumina, silica-alumina, silica-magnesia, silica-alumina-magnesia, titania, silica-titania, and zirconia; more preferably, silica-alumina and silica-alumina-magnesia.

[0108] In addition, the carrier may contain a single or multiple types of metal components selected from alkali metals (Li, Na, K, Rb, Cs), alkaline earth metals (Be, Mg, Ca, Sr, Ba), and rare earth metals (La, Ce, Pr). As for the supported metal component, it is preferable that it be formed into an oxide by calcination, such as with nitrates or acetates.

[0109] Preferably, a carrier comprising an aluminum-containing silica-based composition containing silica and aluminum is used as the carrier. That is, it is preferable for the carrier to contain silica and alumina. The carrier has high water resistance compared to silica and high acid resistance compared to alumina. Furthermore, it possesses superior physical properties compared to conventionally used carriers, such as being hard and having high mechanical strength compared to activated carbon, and moreover, it can stably support the active components, which are oxidized nickel and / or cobalt and X. As a result, the catalyst for the production of carboxylic acid esters can maintain high reactivity over a long period.

[0110] A catalyst for producing carboxylic acid esters, having a specific atomic ratio of oxidized nickel and / or cobalt and X and using an aluminum-containing silica-based composition as a support, when used as a catalyst for chemical synthesis, possesses a high surface area suitable for use as a catalyst support, while also having high mechanical strength and physical stability, and furthermore satisfies corrosion resistance against the liquid properties inherent to the reaction.

[0111] Hereinafter, the characteristics of a carrier comprising an alumina-containing silica-based composition containing silica and alumina according to the present embodiment, which enabled a significant improvement in catalyst lifespan, will be described. The reason why the mechanical strength and chemical stability of the carrier could be significantly improved is presumed as follows.

[0112] It is believed that a carrier comprising an aluminum-containing silica-based composition significantly improves hydrolysis stability (hereinafter simply referred to as "water resistance") by adding aluminum (Al) to the uncrosslinked silica (Si-O) chains of silica gel, thereby newly forming Si-O-Al-O-Si bonds and strengthening the Si-O bonds through the formation of an Al crosslinking structure without losing the original stability of the Si-O chains against acidic substances. Furthermore, it is believed that when the Si-O-Al-O-Si crosslinking structure is formed, the uncrosslinked Si-O chains decrease and the mechanical strength increases compared to the case of silica gel alone. In other words, it is presumed that the amount of Si-O-Al-O-Si structure formed is correlated with the improvement in the mechanical strength and water resistance of the resulting silica gel.

[0113] One of the reasons why nickel and / or cobalt in an oxidized state and X can be stably supported on a carrier for a long period of time is that the carrier has significantly improved mechanical strength and chemical stability as described above, and possesses superior physical properties compared to conventional carriers. As a result, it is believed that the active ingredients nickel and / or cobalt and X are difficult to peel off, allowing them to be stably supported over a long period of time.

[0114] In commonly used carriers, such as silica or silica-titania, the leaching of nickel and / or cobalt components was observed, albeit slowly, during long-term reactions. In contrast, the inventors have discovered that when the above-mentioned carrier is used, the leaching of nickel and / or cobalt components is suppressed over a long period. From the results of X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM / EDX), and bicrystalline high-resolution X-ray fluorescence analysis (HRXRF), it was confirmed that when a silica or silica-titania carrier is used, the leached nickel and / or cobalt components are nickel oxide or cobalt oxide present alone on the carrier. Since nickel oxide or cobalt oxide are compounds soluble in acid, when used as a catalyst for the synthesis of carboxylic acid esters, it is presumed that they were leached by acidic substances, such as methacrylic acid or acrylic acid, which are by-products inherent to this reaction.

[0115] From the analysis of the chemical state of nickel and / or cobalt by two-crystal high-resolution fluorescence X-ray analysis (HRXRF), it is presumed that the nickel and / or cobalt in the catalyst for producing carboxylic acid esters of the present embodiment is not only nickel oxide and / or cobalt oxide as single compounds, but also complex oxides containing nickel and / or cobalt, such as nickel oxide compounds or solid solutions or mixtures thereof, formed by combining nickel oxide and / or cobalt oxide with constituent elements of a carrier.

[0116] High-resolution X-ray fluorescence analysis (HRXRF) has a very high energy resolution, allowing for the analysis of chemical states from the energy positions (chemical shifts) or shapes of the obtained spectra. In particular, in the Kα spectra of 3d transition metal elements, changes in chemical shifts or shapes appear depending on changes in valence or electronic states, allowing for a detailed analysis of the chemical state. In the catalyst for the production of carboxylic acid esters of this embodiment, changes appeared in the NiKα spectrum, confirming a chemical state of nickel different from that of nickel oxide, which is a single compound.

[0117] For example, nickel almite, which is produced from nickel oxide and alumina, is a compound that is insoluble in acid. It is estimated that as a result of the formation of such nickel compounds on a carrier, the leaching of nickel components is significantly improved.

[0118] The preferred elemental composition of a carrier comprising an aluminum-containing silica-based composition including silica and alumina is such that the amount of aluminum is in the range of 1 to 30 mol%, preferably 5 to 30 mol%, and more preferably 5 to 25 mol% with respect to the total molar amount of silicon and aluminum. When the amount of aluminum is within the above range, acid resistance and mechanical strength tend to be good.

[0119] In addition, regarding the catalyst for producing carboxylic acid esters according to the present embodiment, it is preferable that the carrier further comprises, in addition to silica and alumina, an oxide of at least one basic metal selected from alkali metals, alkaline earth metals, and rare earth metals, in order to further improve mechanical strength and chemical stability. Examples of alkali metals as basic metal components include Li, Na, K, Rb, and Cs; examples of alkaline earth metals include Be, Mg, Ca, Sr, and Ba; and examples of rare earth metals include La, Ce, and Pr. Among the above, Mg is preferred as an alkaline earth metal, and it is particularly preferable that the carrier comprises silica, alumina, and magnesia.

[0120] The elemental composition of the carrier, comprising silica, alumina, and an oxide of at least one basic metal such as an alkali metal, an alkaline earth metal, and a rare earth metal, is such that the amount of aluminum is in the range of 1 to 30 mol%, preferably 5 to 30 mol%, and more preferably 5 to 25 mol% with respect to the total molar amount of silicon and aluminum. In addition, the compositional ratio of the basic metal oxide to the alumina is the atomic ratio of (alkali metal + 1 / 2 × alkaline earth metal + 1 / 3 × rare earth metal) / Al, preferably in the range of 0.5 to 10, more preferably 0.5 to 5.0, and even more preferably 0.5 to 2.0. When the elemental composition of the silica, alumina, and basic metal oxide is within the above range, silicon, aluminum, and the basic metal oxide form a specific stable bonding structure, and as a result, the mechanical strength and water resistance of the carrier tend to be good.

[0121] Next, a preferred method for preparing a carrier is described using an example of using an aluminum-containing silica-based composition including silica and alumina, but the method for preparing a carrier is not limited to the following. That is, an aluminum-containing silica-based composition is prepared by reacting a silica sol with an aluminum compound solution, and thereby a carrier is prepared.

[0122] In the example described above, a silica sol is used as the silica source. In this case, it is preferable to mix the silica sol with an aluminum compound to obtain a mixture sol containing the silica sol and the aluminum compound, perform a multi-stage hydrothermal reaction at 20 to 100°C for 1 to 48 hours, then dry to obtain a gel, and calcin it under the temperature, time, and atmosphere conditions described below, or to add an alkaline aqueous solution to the mixture sol to co-precipitate the silica and the aluminum compound, and then calcin it under the conditions described below after drying. In addition, it is also possible to obtain a carrier containing an aluminum-containing silica-based composition having a desired particle diameter by processes such as pulverizing the mixture sol as is using a spray dryer, or drying the mixture sol to granulate the gel.

[0123] Regarding a method for preparing a carrier comprising silica, alumina, and an oxide of at least one basic metal, such as an alkali metal, an alkaline earth metal, and a rare earth metal, the carrier can be prepared by drying a slurry in which an alkali metal compound, an alkaline earth metal compound, and / or a rare earth metal compound are mixed with silica and aluminum components according to the method for preparing a carrier comprising an aluminum-containing silica-based composition comprising silica and alumina described above, and also by calcining it under the conditions described below.

[0124] As for the raw materials for alkali metals, alkaline earth metals, and rare earth metals, generally commercially available compounds can be used, just as with aluminum raw materials. Preferably, they are water-soluble compounds, and more preferably, hydroxides, carbonates, nitrates, and acetates.

[0125] As another preparation method, a method of adsorbing a basic metal component selected from alkali metals, alkaline earth metals, and rare earth metals onto a carrier comprising an aluminum-containing silica-based composition may be utilized. For example, a method using an immersion method, such as adding the carrier to a liquid in which a basic metal compound is dissolved and performing a drying treatment, or a method using an impregnation method, such as allowing a basic compound of the pore volume to permeate the carrier and performing a drying treatment, may be applied. However, regarding the subsequent method of adsorbing the basic metal component, care must be taken, such as performing the liquid drying treatment under gentle conditions, to ensure high dispersion of the basic metal component on the carrier.

[0126] In addition, inorganic or organic materials may be added to the mixed slurry of the various raw materials described above to control the characteristics of the slurry, such as the pore structure of the product, or to finely adjust the physical properties of the resulting carrier.

[0127] Specific examples of inorganic materials used include minerals such as nitric acid, hydrochloric acid, and sulfuric acid; metal salts such as alkali metals such as Li, Na, K, Rb, and Cs; alkaline earth metals such as Mg, Ca, Sr, and Ba; and water-soluble compounds such as ammonia and ammonium nitrate, as well as clay minerals that disperse in water to form a suspension. In addition, specific examples of organic materials include polymers such as polyethylene glycol, methylcellulose, polyvinyl alcohol, polyacrylic acid, and polyacrylamide.

[0128] Although the effects of adding inorganic and organic materials are diverse, they mainly involve the molding of spherical carriers and the control of pore diameter and pore volume; specifically, the liquid quality of the mixed slurry is an important factor in obtaining spherical carriers. By adjusting the viscosity or solid content concentration using inorganic or organic materials, the liquid quality can be changed to one that facilitates obtaining spherical carriers. Furthermore, pore diameter and pore volume can be controlled by a multi-stage hydrothermal synthesis process of the mixed slurry described later. Additionally, it is desirable to appropriately select and use an optimal organic compound that remains inside the carrier during the molding stage and can be removed through firing and cleaning operations after molding.

[0129] (Method for preparing a catalyst for the production of carboxylic acid esters)

[0130] Although the method for manufacturing a catalyst for producing carboxylic acid esters is not particularly limited, according to the following method, it becomes easy to obtain a catalyst for producing carboxylic acid esters having a volume density within a predetermined range and a particle size distribution according to the present embodiment.

[0131] A preferred method for manufacturing a catalyst for producing a carboxylic acid ester according to the present embodiment comprises: a process I of spray-drying a mixed slurry in a dryer using a rotating disc method; a process II of calcining the obtained spray-dried product to obtain a carrier; and a process III of supporting catalyst metal particles on the carrier. Furthermore, in the method for manufacturing a catalyst for producing a carboxylic acid ester according to the present embodiment, in process I, the feed amount of the mixed slurry sprayed with respect to the radius in the transverse direction of the spray dryer is 5×10 -3 70×10 m² / Hr or more -3 It is less than or equal to ㎡ / Hr, and the circumferential speed of the disc is between 10 m / s and 120 m / s.

[0132] According to the method described above, it is easy to obtain a volume density and particle size distribution within a predetermined range in the catalyst for producing carboxylic acid esters according to the present embodiment, thereby enabling the production of a catalyst for producing carboxylic acid esters that exhibits high activity while suppressing the outflow of the catalyst.

[0133] When preparing the mixed slurry used in Process I of the present embodiment, for example, stirring operations of the raw material mixture can be performed while appropriately adjusting the heating conditions.

[0134] The carrier in this embodiment can be manufactured by spray-drying a mixed slurry containing the various raw materials and additives described above, as in Process I to Process II. For the method of atomizing the mixed slurry, known spray devices such as a rotary disc type, a two-fluid nozzle type, or a pressurized nozzle type may be used.

[0135] It is desirable to use the sprayed liquid (mixed slurry) in a well-mixed state (a state in which each component is well dispersed). When in a good mixed state, adverse effects on the performance of the carrier, such as reduced durability due to uneven distribution of each component, tend to be reduced. In particular, when mixing raw material liquids, there is a concern that non-uniform particles may be formed, as there may be an increase in the viscosity of the slurry and some gelation (condensation of colloids). Therefore, in addition to taking care such as mixing the raw materials slowly under stirring, it is also desirable to control the mixture to the metastable region of the silica sol, for example, around pH 2, by adding acid or alkali.

[0136] It is desirable for the liquid to be sprayed (mixed slurry) to have a certain viscosity and solid content concentration. If the viscosity or solid content concentration is above a certain level, it tends to prevent the porous body obtained by spray drying from becoming a sunken sphere rather than a solid sphere. In addition, if the viscosity or solid content concentration is below a certain level, it tends to contribute to the formation of stable droplets in addition to ensuring dispersibility among the porous bodies. Furthermore, the change in viscosity (final Δ viscosity) over one hour from one hour before the start of spray drying (state of raw material mixture) to spraying (state of mixed slurry) tends to affect the particle size distribution and bulk density obtained by spray drying.

[0137] From the above perspective, the final Δ viscosity is preferably less than 10 mPa·s / Hr, more preferably 7 mPa·s / Hr or less, and even more preferably 5 mPa·s / Hr or less. The lower limit of the final Δ viscosity is not particularly limited, but is, for example, 0 mPa·s / Hr or higher. The final Δ viscosity can be measured based on the method described in the examples described below.

[0138] In addition, it is desirable for the solid content concentration to be within the range of 10 to 50 mass% in terms of shape, bulk density, and particle diameter.

[0139] In addition, the tip speed of the stirring blade when stirring the raw material mixture is not particularly limited, but from the perspective of controlling the final Δ viscosity, it is preferably 3 m / s or more and 9 m / s or less, more preferably 4 m / s or more and 8 m / s or less, and even more preferably 5 m / s or more and 7 m / s or less.

[0140] When spray-drying a mixed slurry in a dryer using a rotary disc method, the following conditions are preferred. A rotary disc dryer is equipped with a disc, such as an atomizer. By spraying the mixed slurry with the disc, the bulk density and particle size distribution of the dried product can be adjusted.

[0141] Specifically, the feed amount of the sprayed liquid relative to the horizontal radius of the spray dryer is 5×10 -3 70×10 m² / Hr or more -3 It is desirable to have an area of ​​㎡ / Hr or less, and 10×10 -3 ㎡ / Hr or more 50×10 -3 It is more desirable for m² / Hr or less to be 20×10 -3 ㎡ / Hr or more 40×10 -3 It is more desirable to have a m² / Hr or less.

[0142] In addition, the circumferential speed of the disc is preferably 10 m / s or more and 120 m / s or less, more preferably 20 m / s or more and 100 m / s or less, and even more preferably 30 m / s or more and 90 m / s or less.

[0143] The calcination temperature of the carrier is generally selected within the range of 200 to 800°C. Calcining at temperatures exceeding 800°C is undesirable because it tends to cause a significant decrease in the specific surface area. Additionally, while the calcination atmosphere is not particularly limited, calcination is generally performed in air or nitrogen. Furthermore, the calcination time can be determined based on the specific surface area after calcination, but is generally 1 to 48 hours. Since calcination conditions alter the physical properties of the carrier, such as porosity, it is necessary to select appropriate temperature and temperature increase conditions. If the calcination temperature is excessively low, it tends to be difficult to maintain durability as a composite oxide, while if it is excessively high, there is a risk of a decrease in pore volume. Additionally, regarding temperature increase conditions, it is desirable to gradually increase the temperature using programmed temperature increase or similar methods. Calcining at rapidly high temperatures is undesirable because it leads to severe gasification or combustion of inorganic and organic materials, and exposure to high temperatures exceeding the set level causes pulverization.

[0144] In addition, the particle size distribution can be controlled by adding a classification process after calcination or catalyst support. Examples of classification devices include sieves, vibrating sieves, inertial classifiers, forced vortex centrifugal classifiers, and free vortex classifiers such as cyclones.

[0145] The specific surface area of ​​the carrier is preferably 10 m² / g or more, more preferably 20 m² / g or more, and even more preferably 50 m² / g or more, based on measurement by the BET nitrogen adsorption method, in terms of ease of supporting composite particles, reaction activity when used as a catalyst, difficulty of detachment, and reaction activity. In addition, there are no particular limitations in terms of activity, but in terms of mechanical strength and water resistance, it is preferably 700 m² / g or less, more preferably 350 m² / g or less, and even more preferably 300 m² / g or less.

[0146] Although the exfoliation properties of the supported metal tend to be good when the pore diameter of the support is smaller than 3 nm, when used as a catalyst in liquid-phase reactions, it is preferable for the pore diameter to be 3 nm or larger to maintain high reaction activity without making the diffusion process of the reaction substrate rate-limiting and without increasing the diffusion resistance within the pores excessively high. On the other hand, it is preferable for the diameter to be 50 nm or less to ensure that the supported material is less prone to breakage and that the supported metal is less prone to exfoliation. Therefore, the pore diameter of the support is preferably 3 nm to 50 nm, and more preferably 3 nm to 30 nm. A pore volume is necessary because there are pores that support the composite nanoparticles. However, as the pore volume increases, there is a tendency for strength to decrease rapidly. Therefore, from the perspective of strength and supporting properties, the pore volume is preferably in the range of 0.1 to 1.0 mL / g, and more preferably in the range of 0.1 to 0.5 mL / g. It is preferable that the carrier of the present embodiment has a pore diameter and a pore volume that both satisfy the above range.

[0147] Depending on the reaction type, the shape of the support is selected in the stationary phase as a hollow cylindrical or honeycomb shape, which has a structure with low pressure loss, while in the liquid phase slurry-suspension condition, it is generally spherical and selected to use a shape with an optimal particle diameter for reactivity and separation method. For example, when employing a catalyst separation process by simple sedimentation separation, a particle diameter of 10 to 200 μm is preferred in terms of balance with reaction characteristics, more preferably 20 to 150 μm, and even more preferably 30 to 150 μm. In the cross-filter method, small particles of 0.1 to 20 μm or less are preferred because they have higher reactivity. By changing the type and shape according to these purposes, it can be used as a catalyst for chemical synthesis.

[0148] The amount of nickel or cobalt in an oxidized state loaded onto the carrier is not particularly limited, but is typically 0.01 to 20 mass%, preferably 0.1 to 10 mass%, more preferably 0.2 to 5 mass%, and even more preferably 0.5 to 2 mass% as nickel or cobalt with respect to the mass of the carrier. The amount of X loaded onto the carrier is typically 0.01 to 10 mass%, preferably 0.1 to 5 mass%, more preferably 0.2 to 2 mass%, even more preferably 0.3 to 1.5 mass%, and particularly preferably 0.5 to 1.0 mass% as metal with respect to the mass of the carrier.

[0149] In addition, in this embodiment, there exists a suitable range for the atomic ratio between nickel and / or cobalt and the constituent elements of the carrier. When using a carrier comprising an aluminum-containing silica-based composition including silica and alumina in this embodiment, the compositional ratio of nickel or cobalt and alumina in the catalyst is preferably 0.01 to 1.0, more preferably 0.02 to 0.8, and even more preferably 0.04 to 0.6 as a Ni / Al atomic ratio or Co / Al atomic ratio. In addition, when using a carrier comprising silica, alumina, and an oxide of at least one basic metal such as an alkali metal, an alkaline earth metal, and a rare earth metal, the compositional ratio of nickel or cobalt and alumina in the carrier is preferably 0.01 to 1.0, more preferably 0.02 to 0.8, and even more preferably 0.04 to 0.6 as the Ni / Al atomic ratio or Co / Al atomic ratio, and the compositional ratio of nickel or cobalt and the basic metal component is preferably 0.01 to 1.2, more preferably 0.02 to 1.0, and even more preferably 0.04 to 0.6 as the Ni / (alkali metal + alkaline earth metal + rare earth metal) atomic ratio or Co / (alkali metal + alkaline earth metal + rare earth metal) atomic ratio.

[0150] When the atomic ratio of nickel and / or cobalt with the carrier constituent elements, such as aluminum and basic metal oxides, is within the above range, the effect of improving the leaching of nickel and / or cobalt and the structural change of the supported particles tends to increase. This is thought to be because, within the above range, nickel and / or cobalt, aluminum, and basic metal oxides form specific complex oxides, thereby forming a stable bonding structure.

[0151] The catalyst for producing carboxylic acid esters according to the present embodiment may contain a third component element in addition to nickel and / or cobalt in an oxidized state and X as active components. As the third component element, for example, titanium, vanadium, chromium, manganese, iron, zinc, gallium, zirconium, niobium, molybdenum, rhodium, cadmium, indium, tin, antimony, tellurium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, mercury, thallium, lead, bismuth, aluminum, boron, silicon, and phosphorus may be included. The content of these third component elements in the support is preferably 0.01 to 20 mass%, more preferably 0.05 to 10 mass%. In addition, the catalyst for producing carboxylic acid esters may contain at least one metal component selected from alkali metals, alkaline earth metals, and rare earth metals. The content of alkali metals, alkaline earth metals, and rare earth metals is preferably selected in the range of 15 mass% or less within the support.

[0152] In addition, these third component elements, or alkali metals, alkaline earth metals, and rare earth metals, may be included in the support material during the preparation or reaction of the catalyst for producing carboxylic acid esters, or a method of including them in the support material in advance may be used.

[0153] The specific surface area of ​​the catalyst for producing carboxylic acid esters in this embodiment is preferably 20 to 350 m² / g, more preferably 50 to 300 m² / g, and even more preferably 100 to 250 m² / g, in terms of reaction activity and the difficulty of active components escaping, as measured by the BET nitrogen adsorption method.

[0154] The pore diameter of the catalyst for the production of carboxylic acid esters is derived from the pore structure of the support. Although the exfoliation properties of the supported metal component tend to be good when the diameter is smaller than 3 nm, it is preferable for the pore diameter to be 3 nm or larger when used as a catalyst in liquid-phase reactions, etc., in order to maintain high reaction activity without making the diffusion process of the reaction substrate rate-limiting and without making the diffusion resistance within the pores excessively large. On the other hand, it is preferable for the diameter to be 50 nm or less in order to make the supported material less prone to breakage and the supported composite particles less prone to exfoliation. Accordingly, the pore diameter of the catalyst for the production of carboxylic acid esters is preferably 3 nm to 50 nm, more preferably 3 nm to 30 nm, and even more preferably 3 nm to 10 nm. The pore volume is preferably in the range of 0.1 to 1.0 mL / g, more preferably 0.1 to 0.5 mL / g, and even more preferably 0.1 to 0.3 mL / g in terms of supporting properties and reaction properties. In the catalyst for producing carboxylic acid esters according to the present embodiment, it is preferable that the pore diameter and pore volume together satisfy the above range.

[0155] [Method for preparing a catalyst for the production of carboxylic acid esters]

[0156] The method for manufacturing the catalyst for producing carboxylic acid esters according to the present embodiment is not particularly limited, but may include the following preferred processes. Each process will be described below.

[0157] As a first step, a water slurry comprising a carrier supporting an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals is mixed with an acidic aqueous solution of a soluble metal salt comprising nickel and / or cobalt and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper). The temperature of the mixture of the two liquids is adjusted so that the temperature of the mixture is 60°C or higher. Within the mixture, a precursor of a catalyst for the production of a carboxylic acid ester is formed in which the nickel and / or cobalt and X components are precipitated on the carrier.

[0158] Next, as a second process, a catalyst for producing a carboxylic acid ester can be obtained by washing and drying the precursor obtained in the first process as needed, and then heat treating it.

[0159] According to this method, a catalyst for producing carboxylic acid esters can be obtained having a support layer in which composite particles are localized, and a region including the center of the support that does not contain composite particles.

[0160] In this embodiment, prior to the first process, it is preferable to perform an aging process in which a carrier supported with an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals is aged in water. By aging the carrier in advance, a distribution layer of sharper composite particles can be obtained. The effect of aging the carrier is inferred from the results of measuring the pore distribution by the nitrogen adsorption method to be due to the rearrangement of the carrier's pore structure, resulting in a more uniform and sharp pore structure. The aging temperature of the carrier can be room temperature, but since the change in the pore structure is slow, it is preferable to select a temperature higher than room temperature, in the range of 60 to 150°C. When performed at atmospheric pressure, a range of 60 to 100°C is preferable. In addition, the aging treatment time varies depending on the temperature conditions, but for example, at 90°C, it is preferably 1 minute to 5 hours, more preferably 1 to 60 minutes, and even more preferably 1 to 30 minutes. As for the operation of the first process, the carrier may be used after being aged, dried, and calcined once, but it is preferable to contact a slurry in which the carrier is dispersed in water with an acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X to immobilize the nickel and / or cobalt and X components onto the carrier insolublely.

[0161] Examples of soluble metal salts containing nickel used in the preparation of catalysts include nickel nitrate, nickel acetate, and nickel chloride. Additionally, examples of soluble metal salts containing X include, for instance, when palladium is selected as X, palladium chloride and palladium acetate; when ruthenium is selected, ruthenium chloride and ruthenium nitrate; when gold is selected, gold chloride, sodium gold chloride, potassium dicyanoacid, gold trichloride, and gold cyanide; and when silver is selected, silver chloride and silver nitrate.

[0162] The concentration of each aqueous solution containing nickel and / or cobalt and X is typically in the range of 0.0001 to 1.0 mol / L, preferably 0.001 to 0.5 mol / L, and more preferably 0.005 to 0.2 mol / L. The ratio of nickel or cobalt and X in the aqueous solution is preferably in the range of 0.1 to 10 as the Ni / X atomic ratio or Co / X atomic ratio, more preferably 0.2 to 5.0, and even more preferably 0.5 to 3.0.

[0163] The temperature at which the carrier is contacted with an acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X is one of the important factors controlling the distribution of composite particles, and depends on the amount of oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals that is pre-supported on the carrier, but if the temperature is excessively low, the reaction slows down and the distribution of composite particles tends to widen. In the manufacturing method of the present embodiment, from the perspective of obtaining a support layer localized with sharper composite particles, the temperature at which the carrier is contacted with an acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X is a temperature at which a high reaction rate is obtained, preferably 60°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and particularly preferably 90°C or higher. Since the acidic aqueous solution and the water slurry can be mixed such that the temperature of the mixture exceeds 60°C, it is acceptable to heat the water slurry to the point where the mixture exceeds 60°C even when the acidic aqueous solution is added, or conversely, to heat only the acidic aqueous solution. Of course, it is also acceptable to heat both the acidic aqueous solution and the water slurry to 60°C or higher.

[0164] The reaction may be carried out under pressure at a temperature above the boiling point of the solution, but for ease of operation, it is generally preferable to carry out the reaction at a temperature below the boiling point. The time for immobilizing nickel and / or cobalt and X is not particularly limited and varies depending on conditions such as the carrier type, the loading amount and ratio of nickel and / or cobalt and X, but is typically within the range of 1 minute to 5 hours, preferably 5 minutes to 3 hours, and more preferably 5 minutes to 1 hour.

[0165] The method for preparing a catalyst for producing a carboxylic acid ester according to the present embodiment is based on the principle of immobilizing nickel and / or cobalt and X components in an insoluble manner by chemically reacting an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals, which is pre-supported on a carrier, with a soluble metal salt containing nickel and / or cobalt and X. In order to make the complexation of nickel and / or cobalt and X components more sufficient, it is preferable to immobilize them simultaneously from a mixed aqueous solution of both components.

[0166] In addition, in the manufacturing method of the present embodiment, it is preferable that the water slurry comprising a carrier supporting an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals and rare earth metals contains at least one basic metal salt selected from the group consisting of alkali metals, alkaline earth metals and rare earth metals.

[0167] Accordingly, the generation of metallic black of X can be suppressed, the composite formation of nickel and / or cobalt with X can be promoted, and furthermore, the distribution of composite particles can be controlled more precisely. This effect is presumed to be due to controlling the rate of the chemical reaction between the basic metal oxide pre-supported on a carrier and the soluble metal salt containing nickel and / or cobalt and X by adding at least one metal salt selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals into an aqueous solution.

[0168] For at least one basic metal salt selected from the group consisting of alkali metals, alkaline earth metals and rare earth metals, one or more types selected from water-soluble salts such as organic salts, nitrates, chlorides, etc. of these metals may be used.

[0169] The amount of at least one basic metal salt selected from the group consisting of the above alkali metals, alkaline earth metals, and rare earth metals varies depending on the amount or ratio of nickel and / or cobalt and component X, and is also determined by the amount of basic metal oxide pre-supported on a carrier. Typically, it is 0.001 to 2 times molar, preferably 0.005 to 1 times molar, with respect to the amount of nickel and / or cobalt and component X in the aqueous solution.

[0170] In addition, it is preferable that a water slurry comprising a carrier supporting an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals contains a soluble aluminum salt. In the case of the soluble aluminum salt, aluminum chloride or aluminum nitrate may be used.

[0171] By adding a soluble aluminum salt to a water slurry, an outer layer that substantially does not contain composite particles can be formed on the outer side of the support layer in which the composite particles are localized. This is also based on the principle of insoluble immobilization described above. Soluble salts such as aluminum chloride and aluminum nitrate are used as the soluble aluminum salt, and by a chemical reaction with a basic metal oxide pre-supported on the support, aluminum is reacted on the outer surface of the support to consume the reaction field of nickel and / or cobalt and X, and the nickel and / or cobalt and X components are also immobilized by reaction with the basic metal oxide inside.

[0172] The amount of aluminum component varies depending on how many μm the thickness of the layer that does not support nickel and / or cobalt and X component is set to, and is also determined by the amount of basic metal oxide pre-supported on the carrier. Typically, it is 0.001 to 2 times molar, preferably 0.005 to 1 times molar, relative to the amount of basic metal oxide supported on the carrier.

[0173] Although there are many unclear details regarding the mechanism by which the distribution of nickel and / or cobalt and X components is achieved, it is presumed that this is because the balance between the diffusion rate of the soluble component containing nickel and / or cobalt and X within the carrier and the rate at which the component becomes insoluble through chemical reaction is well maintained under the conditions of the present embodiment, thereby enabling the immobilization of composite particles in an extremely narrow area near the surface of the carrier.

[0174] In addition, when an outer layer is formed on the outer surface of a carrier that does not substantially contain composite particles, the basic metal component that can react with nickel and / or cobalt and X components near the outer surface of the carrier is reacted with aluminum to consume the basic metal component that can react with the nickel and / or cobalt and X components near the outer surface of the carrier, and then nickel and / or cobalt and X are supported, it is presumed that the nickel and / or cobalt and X are immobilized by reacting with the basic metal oxide inside the carrier because the reactive basic metal component near the outer surface of the carrier has already been consumed.

[0175] Next, the second process will be explained.

[0176] Prior to the heat treatment of the second process, the first precursor is washed and dried as needed. The heating temperature of the first precursor is typically 40 to 900°C, preferably 80 to 800°C, more preferably 200 to 700°C, and even more preferably 300 to 600°C.

[0177] The atmosphere for the heat treatment is air (or atmosphere), an oxidizing atmosphere (oxygen, ozone, nitrogen oxides, carbon dioxide, hydrogen peroxide, hypochlorous acid, inorganic / organic peroxides, etc.), or an inert gas atmosphere (helium, argon, nitrogen, etc.). The heating time can be appropriately selected according to the heating temperature and the amount of the first precursor. In addition, the heat treatment can be performed under atmospheric pressure, pressurized pressure, or reduced pressure.

[0178] After the second process described above, a reduction treatment may be performed in a reducing atmosphere (hydrogen, hydrazine, formalin, formic acid, etc.) if necessary. In that case, a treatment method is selected in which nickel and / or cobalt in an oxidized state are not completely reduced to a metallic state. The temperature and time of the reduction treatment can be appropriately selected depending on the type of reducing agent, the type of X, and the amount of catalyst.

[0179] In addition, after the above heat treatment or reduction treatment, oxidation treatment may be performed in air (or atmosphere) or an oxidizing atmosphere (oxygen, ozone, nitrogen oxides, carbon dioxide, hydrogen peroxide, hypochlorous acid, inorganic or organic peroxides, etc.) as needed. In that case, the temperature and time are appropriately selected according to the type of oxidizing agent, the type of X, and the amount of catalyst.

[0180] Third component elements other than nickel and / or cobalt and X may be added during the preparation of the support or under reaction conditions. Alkali metals, alkaline earth metals, and rare earth metals may also be added during the preparation of the catalyst or to the reaction system. Furthermore, the raw materials for the third component elements, alkali metals, alkaline earth metals, and rare earth metals are selected from organic acid salts, inorganic acid salts, hydroxides, etc.

[0181] [Method for manufacturing carboxylic acid esters]

[0182] The catalyst for producing carboxylic acid esters according to the present embodiment can be widely used as a catalyst for chemical synthesis. For example, it can be used for the reaction of producing carboxylic acid esters between aldehydes and alcohols, or for the reaction of producing carboxylic acid esters from alcohols. That is, the method for producing carboxylic acid esters according to the present embodiment may include a process of reacting (a) an aldehyde with an alcohol or (b) one or more types of alcohols in the presence of the catalyst for producing carboxylic acid esters according to the present embodiment and oxygen.

[0183] The catalyst for producing carboxylic acid esters according to the present embodiment exhibits excellent effects, particularly when used as a catalyst for an oxidation reaction. As reaction substrates used in the present embodiment, in addition to the aldehydes and alcohols used in the reaction for producing carboxylic acid esters described in the examples, various reaction substrates may be used, such as alkanes, olefins, alcohols, ketones, aldehydes, ethers, aromatic compounds, phenols, sulfur compounds, phosphorus compounds, oxygen-containing nitrogen compounds, amines, carbon monoxide, water, etc. These reaction substrates may be used individually or as a mixture containing two or more types. From these reaction substrates, various oxidation products such as industrially useful oxygen-containing compounds, oxidation adducts, and oxidative dehydrogenates are obtained.

[0184] Specifically, as reaction substrates, examples include aliphatic alkanes such as methane, ethane, propane, n-butane, isobutane, n-pentane, n-hexane, 2-methylpentane, and 3-methylpentane; and alicyclic alkanes such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane.

[0185] Examples of olefins include aliphatic olefins such as ethylene, propylene, butene, pentene, hexene, heptene, octene, decene, 3-methyl-1-butene, 2,3-dimethyl-1-butene, and allyl chloride; alicyclic olefins such as cyclopentene, cyclohexene, cycloheptene, cyclooctene, and cyclodecene; and aromatic substituted olefins such as styrene and α-methylstyrene.

[0186] Examples of alcohols include saturated and unsaturated aliphatic alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, s-butanol, t-butanol, n-pentanol, n-hexanol, n-heptanol, allyl alcohol, and crotyl alcohol; saturated and unsaturated alicyclic alcohols such as cyclopentanol, cyclohexanol, cycloheptanol, methylcyclohexanol, and cyclohexene-1-ol; aliphatic and alicyclic polyalcohols such as ethylene glycol, propylene glycol, trimethylene glycol, 1,3-butanediol, 1,2-cyclohexanediol, and 1,4-cyclohexanediol; and aromatic alcohols such as benzyl alcohol, salicyl alcohol, and benzhydrol.

[0187] Examples of aldehydes include, for instance, aliphatic saturated aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, isobutylaldehyde, and glyoxal; aliphatic α,β-unsaturated aldehydes such as acrolein, methacrolein, and crotonaldehyde; aromatic aldehydes such as benzaldehyde, tolylaldehyde, benzylaldehyde, and phthalaldehyde, and derivatives of these aldehydes.

[0188] Examples of ketones include aliphatic ketones such as acetone, methyl ethyl ketone, diethyl ketone, dipropyl ketone, and methyl propyl ketone; alicyclic ketones such as cyclopentanone, cyclohexanone, cyclooctanone, 2-methylcyclohexanone, and 2-ethylcyclohexanone; and aromatic ketones such as acetophenone, propiophenone, and benzophenone.

[0189] Examples of aromatic compounds include benzene, toluene, xylene, naphthalene, anthracene, or derivatives thereof substituted with alkyl groups, aryl groups, halogens, sulfonates, etc.

[0190] Examples of phenols include phenol, cresol, xylenol, naphthol, anthrol (hydroxyanthracene), and their derivatives (in which the hydrogen atom of the aromatic ring is substituted with an alkyl group, an aryl group, a halogen atom, a sulfonic acid group, etc.).

[0191] Examples of sulfur compounds include mercaptans such as methyl mercaptan, ethyl mercaptan, propyl mercaptan, benzyl mercaptan, and thiophenol.

[0192] Examples of amines include aliphatic amines such as methylamine, ethylamine, propylamine, isopropylamine, butylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, allylamine, diallylamine, etc.; alicyclic amines such as cyclopentylamine, cyclohexylamine, cycloheptylamine, cyclooctylamine, etc.; and aromatic amines such as aniline, benzylamine, and toluidine.

[0193] These reaction substrates can be used alone or as a mixture containing two or more types. In addition, they do not necessarily need to be purified and may be a mixture with other organic compounds.

[0194] Below, an example of a method for producing a carboxylic acid ester from an aldehyde and an alcohol by an oxidative esterification reaction in the presence of oxygen using the catalyst for producing a carboxylic acid ester of the present embodiment is described.

[0195] As aldehydes used as raw materials, for example, C1-C such as formaldehyde, acetaldehyde, propionaldehyde, isobutylaldehyde, and glyoxal 10 Aliphatic saturated aldehydes; C3-C of acrolein, metacrolein, crotonaldehyde, etc. 10 Aliphatic α·β-unsaturated aldehydes; C6-C of benzaldehyde, tolylaldehyde, benzylaldehyde, phthalaldehyde, etc. 20 Examples include aromatic aldehydes and derivatives of these aldehydes. These aldehydes may be used alone or as a mixture of any two or more. In the present embodiment, it is preferable that the aldehyde be selected from acrolein, metacrolein, or a mixture thereof.

[0196] As alcohols, examples include C1-C of methanol, ethanol, isopropanol, butanol, 2-ethylhexanol, octanol, etc. 10 Aliphatic saturated alcohols; C5-C of cyclopentanol, cyclohexanol, etc. 10 Cyclic alcohols; C2-C of ethylene glycol, propylene glycol, butanediol, etc. 10 Diol; C3-C of allyl alcohol, metallyl alcohol, etc. 10 Aliphatic unsaturated alcohols; C6-C of benzyl alcohol, etc. 20 Examples include aromatic alcohols; hydroxyoxetanes such as 3-alkyl-3-hydroxymethyloxetane. These alcohols may be used alone or as a mixture of any two or more. In the present embodiment, the aldehyde is acrolein and / or metacrolein, and it is preferable that the alcohol is methanol.

[0197] The ratio of aldehyde to alcohol is not particularly limited and can be carried out in a wide range, such as 10 to 1 / 1,000 as the molar ratio of aldehyde / alcohol, but generally it is carried out in the range of 1 / 2 to 1 / 50 as the molar ratio.

[0198] The amount of catalyst used can be significantly varied depending on the type of reaction raw material, the composition or preparation method of the catalyst, reaction conditions, reaction type, etc., and is not particularly limited, but when the catalyst is reacted in a slurry state, it is used so that the solid content concentration in the slurry is preferably within the range of 1 to 50 mass / volume%, more preferably 3 to 30 mass / volume%, and even more preferably 10 to 25 mass / volume%.

[0199] In the production of carboxylic acid esters, any method such as a gas-phase reaction, liquid-phase reaction, or tubular reaction can be carried out in either a batch or continuous manner.

[0200] The reaction can be carried out without a solvent, but it can be carried out using a solvent that is inert to the reaction components, such as hexane, decane, benzene, dioxane, etc.

[0201] The reaction type may also be based on conventionally known types, such as fixed-bed, fluidized-bed, or stirred-bath types. For example, when carried out in a liquid phase, any reactor type such as a bubble tower reactor, a draft tube reactor, or a stirred-bath reactor may be used.

[0202] The oxygen used in the production of carboxylic acid esters can be in the form of molecular oxygen, that is, oxygen gas itself, or a mixed gas in which oxygen gas is diluted with a diluent inert to the reaction, such as nitrogen or carbon dioxide, and air is preferably used as the oxygen source from the perspective of operability and economic efficiency.

[0203] Although the partial pressure of oxygen varies depending on the reaction raw materials, such as aldehydes and alcohols, reaction conditions, or reactor type, in practical terms, it is desirable to manage the partial pressure of oxygen at the reactor outlet to a concentration below the lower limit of the explosion range, for example, between 20 and 80 kPa. The reaction pressure can be carried out over any wide range of pressures, from reduced pressure to increased pressure, but it is typically carried out at a pressure in the range of 0.05 to 2 MPa. Furthermore, from the perspective of safety, it is desirable to set the total pressure (e.g., oxygen concentration of 8%) so that the oxygen concentration of the reactor outlet gas does not exceed the explosion limit.

[0204] When carrying out the reaction for the production of carboxylic acid esters in a liquid phase, it is preferable to add a compound of an alkali metal or alkaline earth metal (e.g., oxide, hydroxide, carbonate, carboxylate) to the reaction system to maintain the pH of the reaction system at 6 to 9. These alkali metal or alkaline earth metal compounds may be used individually or in combination of two or more types.

[0205] The reaction temperature for preparing the carboxylic acid ester can be carried out at a high temperature of 200°C or higher, but is preferably 30 to 200°C, more preferably 40 to 150°C, and even more preferably 60 to 120°C. The reaction time is not particularly limited and cannot be uniquely determined as it depends on the set conditions, but is typically 1 to 20 hours.

[0206] Examples

[0207] The present embodiment will be explained in more detail below with reference to examples, but the present embodiment is not limited in any way by these examples.

[0208] In the following examples and comparative examples, various physical properties were measured by the following method.

[0209] [Measurement of Viscosity of Mixed Slurry]

[0210] The viscosity of the mixed slurry was measured at room temperature at time intervals under the following conditions starting from the start of stirring.

[0211] Viscometer: Brook Digital Viscometer "LVDV1M"

[0212] Spindle: LV-1

[0213] Rotation speed: 100 rpm

[0214] Temperature: Room temperature (25℃)

[0215] The difference between the viscosity immediately before the start of feeding by the spray dryer device and the viscosity one hour before the start of feeding was defined as the final Δ viscosity.

[0216] [Determination of Ni and X loading amounts and Ni / X atomic ratio]

[0217] The concentrations of nickel and X in the composite particles were quantified using an IRIS Intrepid II XDL type ICP emission spectrometer (ICP-AES, MS) manufactured by Thermo Fisher Scientific.

[0218] The sample was prepared by weighing the support material into a Teflon decomposition vessel, adding nitric acid and hydrogen fluoride, heating and decomposing it using an ETHOS TC type microwave decomposition device manufactured by Milestone General, then drying it by evaporation on a heater, and subsequently adding nitric acid and hydrochloric acid to the precipitated residue and pressurizing it using a microwave decomposition device, and the obtained decomposition solution was prepared as a test solution by adding pure water to a certain volume.

[0219] For the quantification method, quantification was performed using the internal standard method with ICP-AES, and the nickel and X content in the catalyst was determined by subtracting the simultaneously performed operation blank value, thereby calculating the loading amount and atomic ratio.

[0220] [Interpretation of the Crystal Structure of Composite Particles]

[0221] Using a Rint2500 powder X-ray diffraction (XRD) manufactured by RIGK, analysis was performed under conditions of an X-ray source Cu tube (40 kV, 200 mA), a measurement range of 5–65 deg (0.02 deg / step), a measurement speed of 0.2 deg / min, and slit widths (scattering, divergence, reception) of 1 deg, 1 deg, and 0.15 mm.

[0222] A method was adopted in which the sample was uniformly spread onto an anti-reflective sample plate and fixed with neoprene rubber.

[0223] [Interpretation of the Chemical State of Metal Components in Composite Particles]

[0224] The analysis was performed using an ESCALAB250 X-ray photoelectron spectrometer (XPS) manufactured by Thermoelectron, under conditions of an excitation source AlKα 15 kV × 10 mA, an analysis area of ​​approximately 1 mm (shape: elliptical), an injection range: survey scan 0–1,100 eV, and narrow scan Ni2p.

[0225] For the measurement sample, the composite particle support was ground and crushed using a mortar and pestle, collected on a powder-specific sample tray, and provided for XPS measurement.

[0226] [Interpretation of Nickel's Chemical State]

[0227] The NiKα spectrum was measured using a Technos XFRA190 type two-crystal high-resolution X-ray fluorescence analyzer (HRXRF), and the various parameters obtained were compared with those of standard materials (nickel metal, nickel oxide) to estimate the chemical state of nickel, such as valence, in the support material.

[0228] The measurement sample was provided for measurement in its original state. The measurement of the Kα spectrum of Ni was performed in partial spectrum mode. At this time, Ge (220) was used as the spectroscopic crystal, and a slit with a longitudinal divergence angle of 1° was used, and the excitation voltage and current were set to 35 kV and 80 mA, respectively. Then, for the standard sample, filter paper was used as the absorber, and for the support sample, the counting time was selected for each sample so that the peak intensity of the Kα spectrum was 3,000 cps or less and 10,000 counts or more for measurement. Five measurements were repeated for each sample, and the metal sample was measured before and after the repeated measurements. After smoothing the measured spectrum (SG method 7 points - 5 times), the peak position, full width at half maximum (FWHM), and asymmetry coefficient (AI) were calculated, and the peak position was treated as the deviation from the measurement value of the metal sample measured before and after the sample measurement, and as the chemical shift (ΔE).

[0229] [Observation of Composite Particle Morphology and Elemental Analysis]

[0230] Using a JEOL 3100 FEF type transmission electron microscope / scanning transmission electron microscope (TEM / STEM) [acceleration voltage 300 kV, equipped with an energy dispersive X-ray detector (EDX)], TEM bright-field images, STEM dark-field images, and STEM-EDS compositional analysis (point analysis, mapping, line analysis) were measured.

[0231] Data interpretation software, TEM and STEM interpretation (length measurement, Fourier transform analysis): Digital Micrograph TMVer. 1.70.16, Gatan, EDS data analysis (mapping image processing, composition quantification calculation): NORAN System SIX ver. 2.0, Thermo Fisher Scientific was used.

[0232] The measurement sample was prepared by crushing the composite particle support with a mortar and pestle, dispersing it in ethanol, performing ultrasonic cleaning for about 1 minute, and then dropping it onto a Mo microgrid and air-drying it to prepare a sample for TEM / STEM observation.

[0233] [Measurement of the ultraviolet-visible spectroscopic spectrum of composite particles]

[0234] Measurements were taken using a V-550 ultraviolet-visible spectrophotometer (UV-Vis) manufactured by Nippon Bunko Co., Ltd. [integrating sphere unit, powder sample holder attached] with a measurement range of 800-200 nm and a scanning speed of 400 nm / min.

[0235] The measurement sample was prepared by grinding and crushing the composite particle support with a mortar and pestle, and then placing it in a powder sample holder for UV-Vis measurement.

[0236] [Observation of the morphology of the carrier and catalyst for the production of carboxylic acid esters]

[0237] The carrier and the catalyst for the production of carboxylic acid esters were observed using an X-650 scanning electron microscope (SEM) manufactured by Hitachi Seisakusho.

[0238] [D of catalyst for the production of carboxylic acid esters 10 , D 50 , D 90 and measurement of half width (W)]

[0239] A 0.2 g catalyst was placed in a beaker, 16 mL of purified water was added, and then a measurement sample was prepared by dispersing for 1 minute using a VCX130 ultrasonic disperser manufactured by SONIC & MATERIALS, INC. This measurement sample was analyzed using an LS230 laser diffraction and scattering particle size distribution analyzer manufactured by Beckmann Coulter to determine the particle diameter D at which the cumulative frequency of the carboxylic acid ester production catalyst reaches x% in the volume-based particle size distribution. x (D 10 , D 50 and D 90 The half-width (W) of the particle size distribution (based on volume) was measured.

[0240] [Specific Surface Area]

[0241] The specific surface area was measured by the BET method using Quantachrome’s Quadrasorb.

[0242] [Measurement of Bulk Density (CBD) of Catalysts for the Production of Carboxylic Acid Esters]

[0243] As a pretreatment, approximately 120 g of the catalyst for the production of carboxylic acid esters was placed in a stainless steel crucible and dried in a muffle furnace at 150°C for 6 hours. After calcination, it was placed in a desiccator (containing silica gel) and cooled to room temperature. Subsequently, 100 g of the pretreated catalyst for the production of carboxylic acid esters was placed in a 250 mL graduated cylinder, and the cylinder was tapped and filled using a shaker for 15 minutes. Afterward, the surface of the sample in the graduated cylinder was flattened, and the filling volume was read. The bulk density was calculated by dividing the mass of the catalyst for the production of carboxylic acid esters by the filling volume.

[0244] [Leakage Rate]

[0245] Based on the total amount of catalyst used in the production of the carboxylic acid ester described below and the amount of remaining catalyst after 500 hours of production of the carboxylic acid ester, the effluent rate was calculated using the following formula.

[0246] Flow rate = {1 - (Amount of remaining catalyst / Amount of catalyst used in the reaction)} × 100 [%]

[0247] Here, the amount of residual catalyst was defined as the mass of the catalyst for producing carboxylic acid esters after 500 hours of production, dried at 130°C for 10 hours.

[0248] In other words, catalysts with a high outflow rate tend to be difficult to remain in the reactor because they are prone to flowing out of the reactor, and thus, during long-term operation, the amount of catalyst provided to the reaction decreases, and consequently, the conversion rate tends to deteriorate.

[0249] [Example 1]

[0250] (Preparation of catalyst for carboxylic acid ester production)

[0251] An aqueous solution prepared by dissolving 3.75 kg of aluminum nitrate nodahydrate, 2.56 kg of magnesium nitrate, and 540 g of 60 mass% nitric acid in 5.0 L of pure water was slowly added dropwise to 20.0 kg of a silica sol solution (SiO2 content 30 mass%) with colloidal particle diameters of 10–20 nm, which was stirred and maintained at 15°C, and the pH was adjusted to 1.8. The raw material mixture (solid content 25 mass%) containing the silica sol, aluminum nitrate, and magnesium nitrate obtained in this way was heated to 55°C. Subsequently, the raw material mixture was stirred for 30 hours at a stirring blade tip speed of 5.5 m / s to obtain a mixed slurry with a final Δ viscosity of 0.5 mPa·s / Hr.

[0252] After that, with the spray dryer device, the Feed rate / SD radius is 25×10 -3 A solid was obtained by spray drying under conditions of a disc (atomizer) circumferential speed of 80 m / s while feeding the slurry to [㎡]. Here, SD radius refers to the radius in the transverse direction in the rotating disc type spray dryer used in this embodiment.

[0253] Next, the obtained solid was packed into an open-top stainless steel container to a thickness of approximately 1 cm, and heated in an electric furnace from room temperature to 300°C over a period of 2 hours, followed by holding for 3 hours. Additionally, the temperature was raised to 600°C over 2 hours and held for 3 hours, after which the material was slowly cooled to obtain a carrier. The obtained carrier contained 83.3 mol%, 8.3 mol%, and 8.3 mol% of silicon, aluminum, and magnesium, respectively, relative to the total molar amount of silicon, aluminum, and magnesium. Furthermore, observation by scanning electron microscope (SEM) revealed that the shape of the carrier was nearly spherical.

[0254] 300 g of the carrier obtained as described above was dispersed in 1.0 L of water heated to 90°C and stirred at 90°C for 15 minutes. Subsequently, an aqueous solution containing 16.35 g of nickel nitrate hexahydrate and 12 mL of a 1.3 mol / L aqueous solution of gold chloride was prepared and heated to 90°C, and this solution was added to the carrier slurry. Stirring was continued at 90°C for another 30 minutes to immobilize the nickel and gold components onto the carrier insolublely.

[0255] Subsequently, the supernatant was removed by settling, washed several times with distilled water, and filtered. This was dried in a dryer at 105°C for 10 hours, and then calcined in air at 450°C for 5 hours in a muffle furnace to obtain a catalyst for producing carboxylic acid esters (composite particle support of NiOAu / SiO2-Al2O3-MgO) supported with 1.05 mass% nickel and 0.91 mass% gold. The Ni / Au atomic ratio of the obtained catalyst for producing carboxylic acid esters was 4.0.

[0256] The obtained composite particle support was embedded in a resin and the sample obtained by polishing was subjected to line analysis of the particle cross-section using an X-ray microprobe (EPMA). As a result, it was confirmed that the carrier had an outer layer that substantially did not contain nickel and gold in the region at a depth of 0.5 μm from the outermost surface, nickel and gold were supported in the region at a depth of 10 μm from the surface, and no composite particles were present inside the carrier.

[0257] Subsequently, the shape of the composite particle carrier was observed using a transmission electron microscope (TEM / STEM), and it was confirmed that spherical nanoparticles with a maximum distribution at 2–3 nm (number average particle diameter: 3.0 nm) were supported on the carrier. When the nanoparticles were observed under further magnification, lattice stripes corresponding to the plane spacing of Au (111) were observed on the nanoparticles. When composition point analysis was performed on individual nanoparticles using STEM-EDS, nickel and gold were detected in every particle. The average value of the nickel / gold atomic ratio of the nanoparticles (number of samples: 50) was 1.05. In addition, when nano-regional analysis was performed on the observed particles, the Ni / Au atomic ratio in the center of the particle was 0.90, and in the edge of the particle it was 2.56. Only trace amounts of nickel were detected in parts other than the particles. When the same measurement was performed on 50 points, a large amount of nickel was detected around the edge of every particle. From EDS elemental mapping, it was observed that the distributions of nickel and gold were nearly identical. Additionally, from the compositional line profile, nickel was distributed one step larger than gold in every scanning direction.

[0258] From the results of powder X-ray diffraction (XRD), no diffraction pattern originating from nickel was observed, and it was confirmed that it exists in an amorphous state. Meanwhile, although it cannot be described as a clear peak, a broad peak corresponding to a gold crystal was present. Although the value was close to the detection limit (2 nm) of powder X-ray diffraction, the average crystallite diameter calculated from Scherrer's equation was about 3 nm. Regarding the chemical state of nickel, it was confirmed from the results of X-ray photoelectron spectroscopy (XPS) that nickel is divalent.

[0259] From the results of the two-crystal high-resolution X-ray fluorescence analysis (HRXRF), the chemical state of nickel was estimated to be the high-spin divalent state of nickel, and it was determined that it is a different chemical state from nickel oxide, a single compound, based on the difference in the NiKα spectrum. The full width at half maximum (FWHM) of the catalyst's NiKα spectrum obtained from the measured spectrum was 3.470, and the chemical shift (ΔE) was 0.335. The full width at half maximum (FWHM) of the NiKα spectrum of nickel oxide measured as a standard material was 3.249, and the chemical shift (ΔE) was 0.344.

[0260] In addition, when the change in the electronic excitation state of this composite particle support was investigated by ultraviolet-visible spectroscopy (UV-Vis), no surface plasmon absorption peak originating from gold nanoparticles near 530 nm appeared, and broad absorption attributed to NiO2 was observed in the wavelength range of 200–800 nm.

[0261] From the above results, it is inferred that the microstructure of the composite particles consists of gold nanoparticles with surfaces covered by nickel in an oxidized state.

[0262] (Evaluation of physical properties of catalysts for the production of carboxylic acid esters)

[0263] The specific surface area of ​​the obtained catalyst for the production of carboxylic acid esters was calculated to be 141 m² / g. In addition, as a result of measuring the particle size distribution of the catalyst for the production of carboxylic acid esters by the laser scattering method, the particle size distribution half-width (W) was 50 μm, and D 50 , D 10 / D 50 , D 90 / D 50 , W / D 50 The values ​​were 60 μm, 0.7, 1.5, and 0.8, respectively. The particle size distribution was a single peak. In addition, the bulk density was measured to be 1.05 g / cm³.

[0264] (Preparation of carboxylic acid esters)

[0265] 240 g of the obtained catalyst for the production of carboxylic acid esters was injected into a stirred stainless steel reactor equipped with a catalyst separator and a liquid phase of 1.2 liters, and the reaction for the production of oxidative carboxylic acid esters from aldehydes and alcohols was carried out while stirring the contents at a tip speed of 4 m / s of the stirring blades. Specifically, a 36.7 mass% methacrolein / methanol solution was continuously supplied to the reactor at 0.6 liters / hr and a 1–4 mass% NaOH / methanol solution at 0.06 liters / hr, and air was blown in at a reaction temperature of 80°C and a reaction pressure of 0.5 MPa so that the outlet oxygen concentration was 8.0 volume%, and the concentration of NaOH supplied to the reactor was controlled so that the pH of the reaction system was 7. The reaction product was continuously removed from the reactor outlet by overflow and its reactivity was investigated by gas chromatography.

[0266] The methacrolein conversion rate at 500 hours from the start of the reaction was 72%, and the selectivity of methyl methacrylate was 95%. In addition, the catalyst outflow rate was 2%.

[0267] [Examples 2–7 and Comparative Examples 1–7]

[0268] A catalyst for the production of carboxylic acid esters was prepared in the same manner as in Example 1, except that the preparation conditions of the mixed slurry and the spray drying conditions during the manufacture of the carrier were changed as shown in Table 1. Specifically, (i) the solid content was adjusted by increasing or decreasing the amount of pure water dissolving aluminum nitrate nonahydrate and magnesium nitrate in the raw material mixture, and (ii) the pH was adjusted by increasing or decreasing the amount of 60 mass% nitric acid, each to the values ​​shown in Table 1. The physical properties of this catalyst for the production of carboxylic acid esters were evaluated in the same manner as in Example 1, and carboxylic acid esters were prepared using this catalyst in the same manner as in Example 1 to calculate the reaction results and the efflux rate of the catalyst. Furthermore, the volume-based particle size distribution of the catalysts in Examples 2 to 7 was a single peak. These results are shown in Table 1.

[0269]

Claims

Claim 1 A catalyst for producing a carboxylic acid ester comprising catalytic metal particles and a carrier supporting said catalytic metal particles, wherein the bulk density of said catalyst for producing the carboxylic acid ester is 0.50 g / cm³ or more and 1.50 g / cm³ or less, and the particle diameter at which the cumulative frequency of the volume-based particle size distribution of said catalyst for producing the carboxylic acid ester becomes x% is D x When doing D 10 / D 50 ≥0.2 and D 90 / D 50 ≤2.5, and when the full width at half maximum of the above particle size distribution is W, W / D 50 Catalyst for the production of carboxylic acid esters, with a value of ≤1.

5. Claim 2 A catalyst for producing a carboxylic acid ester according to claim 1, wherein W is 100 μm or less. Claim 3 A catalyst for producing a carboxylic acid ester according to claim 1 or 2, wherein the catalyst metal particles comprise at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, and gold, silver, and copper. Claim 4 A catalyst for producing a carboxylic acid ester, wherein, in claim 1 or 2, the catalyst metal particles are composite particles comprising one or more of nickel and cobalt in an oxidized state and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper). Claim 5 A catalyst for producing carboxylic acid esters according to claim 4, wherein the compositional ratio of nickel or cobalt and X in the composite particles is 0.1 to 10 as a Ni / X atomic ratio or a Co / X atomic ratio. Claim 6 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the composite particles comprise nickel or cobalt in an oxidized state and gold. Claim 7 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the average particle diameter of the composite particles is 2 to 10 nm. Claim 8 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the supporting layer on which the composite particles are localized exists in an area from the surface of the catalyst for producing a carboxylic acid ester up to 40% of the substantial diameter of the catalyst for producing a carboxylic acid ester. Claim 9 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the substantial diameter of the catalyst for producing the carboxylic acid ester is 200 μm or less, and the supporting layer on which the composite particles are localized exists in a region from the surface of the catalyst for producing the carboxylic acid ester to 30% of the substantial diameter of the catalyst for producing the carboxylic acid ester. Claim 10 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the outer layer, which substantially does not contain the composite particles, is formed on the outer side of the supporting layer in which the composite particles are localized, and the outer layer is formed with a thickness of 0.01 to 15 μm. Claim 11 A catalyst for producing a carboxylic acid ester according to claim 4, wherein the composite particle has a nucleus composed of X, and the nucleus is coated with nickel or cobalt in an oxidized state. Claim 12 A catalyst for producing a carboxylic acid ester according to claim 1 or 2, wherein the carrier comprises silica and alumina. Claim 13 In paragraph 1 or 2, the above D 50 A catalyst for the production of carboxylic acid esters, having a thickness of 10 μm or more and 200 μm or less. Claim 14 A method for producing a carboxylic acid ester, comprising a process of reacting (a) an aldehyde with an alcohol or (b) one or more alcohols in the presence of a catalyst for producing a carboxylic acid ester described in claim 1 or 2 and oxygen. Claim 15 A method for producing a carboxylic acid ester according to claim 14, wherein the aldehyde is one or more of acrolein and metacrolein. Claim 16 A method for preparing a carboxylic acid ester according to claim 14, wherein the aldehyde is one or more of acrolein and metacrolein, and the alcohol is methanol.

Citation Information

Patent Citations

  • Composite particle-loaded article, method for producing the composite particle-loaded article, and method for producing compound using the composite particle-loaded article as chemical synthesis catalyst

    KR1020100061739A